P-58 'When horses run together'; developing collective hospice leadership for the future. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Arnold, Liz
Abstract : Help the Hospices Commission into the Future of Hospice Care 'Preparing for the Future' report (2012), recommends that hospices need to ensure their workforce is fit for purpose; that clear leadership permeates throughout the sector, and that good leadership is not undermined by a 'missing middle tier' of management and practice. A local hospice organisational climate report delivered clear recommendations for leadership development that would impact the performance of individuals, teams and the wider organisation. In response, a bespoke leadership development programme was designed, entitled, 'Leading from the Middle' (LfM), using the 'Future Ambitions for Hospice Care' (2013) report as a strategic framework to ground the learning experience. It was essential that the programme design addressed the issues raised within the climate report and at the same time, empowered staff operating in the middle of the organisation to work on operational challenges and deliver tangible outcomes. The programme incorporated the following critical success factors: Engage a wide group of stakeholders in the delivery of the programme to increase readiness for learning and change, build resilience and a vibrant organisational culture Optimise the hospice vision to energise programme delegates, trustees and the leadership team Promote leadership development as a dynamic process which can be sustained, rather than a 'one-off' investment Create an evaluation model that focuses on output measures to ensure that impact evidence is produced Twenty middle managers from across the organisation attended the LfM programme during 2014. An evaluation of the programme, undertaken in April 2015, using an Appreciative Inquiry methodology, demonstrated that cohort members have a clear understanding of the values, culture and practices of a well-led hospice. There is clear evidence that behaviours associated with a collective leadership culture are being practised, together with a crafting of the foundations for cultural change.